Symptomatic Hyperlactatemia Associated with Nucleoside Analogue Reverse-Transcriptase Inhibitor Use in HIV-Infected Patients: A Report of 24 Cases in a Resource-Limited Setting (Uganda) - Mwebaze Songa, Patricia; Castelnuovo, Barbara; Birabwa Mugasha, Estella; Ocama, Ponsiano; Kambugu, Andrew (Clinical infectious diseases, 2007)
We describe 24 Ugandan patients with human immunodeficiency virus infection who developed symptomatic hyperlactatemia associated with the use of nucleoside analogues. All patients were receiving combination therapy that contained stavudine. The median serum lactate level was 6.6 mmol/L. All patients had their antiretroviral treatment regimen discontinued. Hospital admission was required for 5 patients. Five patients died.
Keywords: Symptomatic Hyperlactatemia; Nucleoside Analogue Reverse-Transcriptase; HIV-Infected Patients